Makanan Halal dan Haram dalam Islam: Konsep, Tantangan Globalisasi, dan Pengaruhnya Terhadap Spiritualitas. - Edi Hermanto,; Salsabila Putri Zalianty,; Sefti Sri Amanda,; Selly Fitriani, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Food is a basic human need that not only serves to maintain physical survival, but also has a significant influence on spiritual condition and quality of worship. In Islam, food consumption is clearly regulated through the concepts of halal and haram based on the Qur'an and Hadith, with the principle of halalan tayyiban as the main guideline. This study aims to examine the concept of halal and haram food from the perspective of the Qur'an, specifically QS. Al-Baqarah verses 168–173, and analyze its relevance to human spiritual life in the era of globalization. This study uses a qualitative method with a library research approach, with data sources in the form of verses from the Qur'an, hadiths of the Prophet Muhammad SAW, tafsir books, and relevant scientific literature. The results of the study show that the halal status of food is not only determined by its ingredients, but also by the processing methods, how it is obtained, and the moral values associated with it. Consuming halal food has a positive effect on purity of heart, peace of mind, and quality of worship, while haram food can harden the heart, weaken spirituality, and prevent prayers from being answered. Amidst the challenges of globalization and the complexity of the modern food industry, the principles of halal and haram remain relevant and demand critical awareness from Muslims in choosing food. Thus, maintaining the halal status of consumption is part of obedience to Allah SWT and an effort to maintain a balance between physical and spiritual needs.